How confident are vocational trainees in making career decisions? - Bakar, Ab. Rahim; Mohamed, Shamsiah; Kazilan, Fitri (The International Journal of the Humanities, 2009)
Career decision-making self-efficacy (CDMSE) denotes individuals’ degree of confidence that they can successfully engage in tasks associated with making a career choice and with commitment to a career (Taylor and Betz, 1983). Studies have shown that career self-efficacy plays significant roles in the development of vocational interests, choice, and behavior (Lent et al., 2002). Helping students identify their beliefs about their abilities to both undertake exploration tasks and make decisions appears to be an important requisite to help them identify patterns of interests (Gushue et al., 2007). Thus, a study was conducted using 850 vocational trainees in Malaysian Vocational Institutions. The career decision-making self-efficacy by Taylor and Betz (1983) was used to measure CDMSE of trainees. A 5-point Likert scale ranging from Not Confidence at all (1) to Completely Confidence (5) was used to assess trainees’ CDMSE. The objective of this study was to determine the career decision-making self-efficacy (CDMSE) among vocational trainees in Malaysia and to compare the trainees’ decision-making abilities between genders. Overall, the career decision-making ability of vocational trainees was high (M=3.96, s.d=.34). However, some aspects of CDMSE need improvement (particularly on problem solving, planning for future, and gathering occupational information). There is a no significant difference in CDMSE between trainees of two different institutions. However, there is a significant difference in CDMSE between genders. Male trainees felt they were more confident in making career decision than female trainees.